Understanding the efficacy of micro-CT to analyse high speed sintering parts. Issue 1 (18th January 2016) - Rouholamin, Davood; Hopkinson, Neil
Abstract : Purpose: – The purpose of this study was to assess the suitability of micro-computed tomography as a non-destructive method to investigate the morphology of nylon 12 parts produced by high-speed sintering (HSS). The investigation of the effect of changes in the lamp power on the properties of the fabricated parts was another purpose of this study. Design/methodology/approach: – Nylon 12 parts were manufactured using HSS with various lamp powers. Morphological properties of the parts were measured using micro-computed tomography. Ultimate tensile strength, elongation at break and Young's modulus of the prepared parts were determined and compared. The effect of lamp power on the properties of the parts was then studied. Findings: – This paper proposes micro-computed tomography as a suitable technique to study the 3D structure of the parts produced by HSS. The effects of lamp power on the properties of the produced parts were also discussed. Practical implications: – The findings could result in an improvement in customisation of the parts for various applications through varying the lamp power. The level of lamp power could be tailored to obtain suitable part properties for a target application. Originality/value: – This study strengthens the fact that HSS is a promising additive manufacturing technique to produce nylon 12 parts, and the properties of the parts could be maximised using a suitable level of lamp power. The results showed that micro-computed tomography could be used as an efficient technique to investigate the morphology of the sintered parts.